An investigation of patch occupancy and dispersal by third to final instar nymphs of Brachytrupes megacephalus Lefèbvre, 1827 (Orthoptera: Gryllidae: Gryllinae) across the sand dune biotope at the Għadira Nature Reserve, Malta - Cassar, Louis-F.; Gauci, Adam; Gauci, Mark; Attard, David; Tomakova, Vera (Zootaxa, 2023)
Dispersal patterns of third, fourth and fifth instar nymphs of the stenoecious gryllid, Brachytrupes megacephalus (Lefèbvre, 1827), are investigated on the sand dune within the Għadira Nature Reserve, a remnant habitat patch forming part of the core area that supports the largest population of the species in Malta. Field investigations were carried out over a period of 11 weeks during a specific 75 minute time window, when nymphs are known to engage in subaerial activity at the mouth of their respective burrow. Climatic variables are examined in relation to abundance, while dispersal patterns are presented. The study shows that the predominant movement of nymphs across the terrain is northward, mainly to the northwest and the north-northeast. The present contribution also provides a summary of recommendations for conservation of the species, including an interdisciplinary approach to habitat management at multiple spatial scales.